2023
DOI: 10.2147/idr.s399484
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Next-Generation Sequencing Assists in the Diagnosis of Mediastinal Aspergillus fumigatus Abscess in an Immunocompetent Patient: A Case Report and Literature Review

Abstract: Background Aspergillus fumigatus is an opportunistic fungal pathogen, which is commonly found in lungs and rarely causes infections in mediastinum. Mediastinal Aspergillus abscess is a serious infectious condition, and is characterized by difficult diagnosis due to its clinical manifestations being nonspecific. Case Presentation Here, we report a case of a mediastinal Aspergillus fumigatus abscess in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In patients with normal immune function, Aspergillus fumigatus was identified through endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) tissue with mNGS. Histological analysis of mediastinal biopsy and tissue fungal culture also indicated Aspergillus fumigatus infection, confirming the detection of mNGS [29]. In an infant patient initially suspected of having a lung tumor, mNGS identified Aspergillus fumigatus in BALF as the causative agent.…”
Section: The Clinical Application Of Mngs In Pulmonary Aspergillosismentioning
confidence: 55%
“…In patients with normal immune function, Aspergillus fumigatus was identified through endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) tissue with mNGS. Histological analysis of mediastinal biopsy and tissue fungal culture also indicated Aspergillus fumigatus infection, confirming the detection of mNGS [29]. In an infant patient initially suspected of having a lung tumor, mNGS identified Aspergillus fumigatus in BALF as the causative agent.…”
Section: The Clinical Application Of Mngs In Pulmonary Aspergillosismentioning
confidence: 55%
“…Peripheral blood mNGS assay has recently been adopted as a supplementary approach to detect infectious microorganisms (Deng et al, 2023). Yet no large sample size studies have comprehensively apprised the clinical values of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…mcfDNA has the potential to identify concurrent infections and unexpected etiological agents in undiagnosed patients, as was noted in a study by Hoenigl et al, wherein reports showed R. microsporus in patients suspected to have CAPA [ 83 ]. In one of the case reports, authors reached the diagnosis of mediastinal aspergillosis merely within a day of sample collection, which was two weeks before culture and five days before histopathological results [ 84 ]. Another study showed A. lentulus as the implicated pathogen, which is difficult to differentiate from A. fumigatus using conventional modalities but requires different antifungal therapy [ 85 ].…”
Section: Other Emerging Modalities Of Nucleic-acid-based Molecular Di...mentioning
confidence: 99%